Factors Influencing Students' Preference of Management Institutes: A Kano Model Analysis - Bhola, Sarang Shankar; Nalawade, Rishikesh Krishnaji (Indian Journal of Marketing, 2013)
The present study aims to find out the expectations of students towards various entities of management institutes viz. library, infrastructure, academics, administration, etc. To identify and classify these expectations, the Kano Model was used. The responses of the students were analyzed by using the Kano Methodology developed by Dr. Kano and the requirements were classified into the Kano attributes i.e. Must be (M), One dimensional (O) and Attractive requirements (A). This Kano methodology included framing a questionnaire, evaluation of Kano parameters through the evaluation criteria like using the Kano Model evaluation table, extent of satisfaction, and extent of dissatisfaction. The research is of diagnostic type conducted in 2011-12 and a structured codified close ended schedule was used to collect the required primary data from students pursuing MBA (two years full time program) from the management institutes affiliated to Shivaji University, Kolhapur, Maharashtra and approved by the AICTE, New Delhi. Graduates from different disciplines like Arts, Commerce, Science, and Professional courses participated in the study. Convenient sampling method was used for data collection. Most parameters were found to be categorized under the one dimensional requirements. Also, it is found that there were uniform preferences for the one dimensional requirements and attractive requirements of the students from different disciplines.